A study of community college presidential qualifications and careerpaths - Weltsch, Michael Duane (Kansas State University, 2009)
This ex post facto research was conducted using parametric and non-parametric analysis to determine if the mass retirement of community college presidents between 2001 and 2007 had precipitated a diminution in educational qualifications, a reduction in pre-presidential community college experience, or a change in presidential career paths of first time community college presidents by era (before and after 2001). Seven hundred eighty-five currently serving presidents of comprehensive community colleges were surveyed. The overall return rate of the survey was 53.25%: the useable return rate was 49.30%. Parametric (independent samples t-test) and non-parametric (Mann-Whitney and chi square) tests were used to determine if there were significant differences in educational qualifications, pre-presidential community college experience, and presidential career paths of first time community college presidents by era (before and after 2001). The study found: - A diminution of the educational qualifications after 2001 with fewer presidents holding doctorates at the time of their first presidential appointments compared to presidents appointed before 2001; - A significant increase in pre-presidential community college experience of presidents appointed after 2001 at the time of their first presidential appointments compared to presidents appointed before 2001; - A significant difference in presidential career paths by era. Specifically, presidents appointed after 2001 were significantly less likely to have entered the community college system from K12 or from non-educational management positions. Presidents appointed after 2001 were also significantly less likely to have served as a community college Chief Academic Officer and significantly more likely to have served as a community college Primary Academic Officer, Chief Students Affairs Officer, or Vice President.
Keywords: Community College Presidents; Career Paths; Education, Administration (0514); Education, Adult and Continuing (0516); Education, Community College (0275); Education, General (0515); Education, Higher (0745)